Molecular signatures of maturing dendritic cells: implications for testing the quality of dendritic cell therapies - Jin, Ping; Han, Tae Hee; Ren, Jiaqiang; Saunders, Stefanie; Wang, Ena; Marincola, Francesco M; Stroncek, David F (Journal of translational medicine, 2010)
Dendritic cells (DCs) are often produced by granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-4 (IL-4) stimulation of monocytes. To improve the effectiveness of DC adoptive immune cancer therapy, many different agents have been used to mature DCs. We analyzed the kinetics of DC maturation by lipopolysaccharide (LPS) and interferon-gamma (IFN-gamma) induction in order to characterize the usefulness of mature DCs (mDCs) for immune therapy and to identify biomarkers for assessing the quality of mDCs. Peripheral blood mononuclear cells were collected from 6 healthy subjects by apheresis, monocytes were isolated by elutriation, and immature DCs (iDCs) were produced by 3 days of culture with GM-CSF and IL-4. The iDCs were sampled after 4, 8 and 24 hours in culture with LPS and IFN-gamma and were then assessed by flow cytometry, ELISA, and global gene and microRNA (miRNA) expression analysis. After 24 hours of LPS and IFN-gamma stimulation, DC surface expression of CD80, CD83, CD86, and HLA Class II antigens were up-regulated. Th1 attractant genes such as CXCL9, CXCL10, CXCL11 and CCL5 were up-regulated during maturation but not Treg attractants such as CCL22 and CXCL12. The expression of classical mDC biomarker genes CD83, CCR7, CCL5, CCL8, SOD2, MT2A, OASL, GBP1 and HES4 were up-regulated throughout maturation while MTIB, MTIE, MTIG, MTIH, GADD45A and LAMP3 were only up-regulated late in maturation. The expression of miR-155 was up-regulated 8-fold in mDCs. DCs, matured with LPS and IFN-gamma, were characterized by increased levels of Th1 attractants as opposed to Treg attractants and may be particularly effective for adoptive immune cancer therapy.